2007
DOI: 10.1007/s11845-007-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of smoke produced by high-frequency electrosurgery

Abstract: This study demonstrated the presence of irritant, carcinogenic and neurotoxic compounds in electrosurgical smoke. This may have considerable implications for the health and safety of all involved in surgical practice, as exposure to these compounds pose potential risks to health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 13 publications
0
56
0
8
Order By: Relevance
“…Many previous studies have investigated particle characterization in surgical smoke and its infection risks (DesCoteaux et al, 1996;Kunachak et al, 1996;Capizzi et al, 1998;Hughes and Hughes, 1998;BruskeHohfeld et al, 2008;Andreasson et al, 2009;Mowbray et al, 2013). However, chemical pollutants such as VOCs in surgical smoke have been addressed by only a few studies (Al Sahaf et al, 2007;Weston et al, 2009;Hill et al, 2012;Mellor and Hutchinson, 2013;Choi et al, 2014) and their impact on the indoor air is rarely discussed. The results of this study indicated that surgical smoke contain large amounts of VOCs, and also showed that the concentrations of several VOCs such as benzene and toluene exceed concentration guidelines such as those published by the WHO, RfC, and REL.…”
Section: Surgical Smoke As Voc Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have investigated particle characterization in surgical smoke and its infection risks (DesCoteaux et al, 1996;Kunachak et al, 1996;Capizzi et al, 1998;Hughes and Hughes, 1998;BruskeHohfeld et al, 2008;Andreasson et al, 2009;Mowbray et al, 2013). However, chemical pollutants such as VOCs in surgical smoke have been addressed by only a few studies (Al Sahaf et al, 2007;Weston et al, 2009;Hill et al, 2012;Mellor and Hutchinson, 2013;Choi et al, 2014) and their impact on the indoor air is rarely discussed. The results of this study indicated that surgical smoke contain large amounts of VOCs, and also showed that the concentrations of several VOCs such as benzene and toluene exceed concentration guidelines such as those published by the WHO, RfC, and REL.…”
Section: Surgical Smoke As Voc Sourcementioning
confidence: 99%
“…It is in relatively recent years that the chemical composition in surgical smoke such as volatile organic compounds (VOCs) has been investigated. Al Sahaf et al (2007) quantified the presence of toluene, ethylbenzene, and xylene in surgical smoke, which appeared in quantities similar to those in cigarette smoke. Hills et al (2012) also reported that chemicals including benzene, toluene, styrene, formaldehyde could be found in surgical smoke.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de los espacios donde se llevan a cabo procedimientos quirúrgicos, los profesionales de la salud constituyen un grupo profesional con elevado riesgo por la complejidad de sus tareas y los factores de riesgo presentes. Por esta razón, en las salas de operaciones la inhalación y contacto con agentes físicos, químicos y biológicos, ponen en riesgo la salud de los trabajadores [1].…”
Section: Introductionunclassified
“…Al Sahaf et al (2007) advised that staff exposed to surgical smoke should be made There is no doubt that diathermy smoke contains compounds that are hazardous to health but it is difficult to conclude to what extent individuals are affected by these compounds. However Al Sahaf et al (2007) state that the only ethically acceptable solution would be to inform those who are exposed to diathermy smoke on a daily basis of this potential hazard and to make them aware of the alternatives.…”
mentioning
confidence: 99%
“…However Al Sahaf et al (2007) state that the only ethically acceptable solution would be to inform those who are exposed to diathermy smoke on a daily basis of this potential hazard and to make them aware of the alternatives. …”
mentioning
confidence: 99%